Food and Nutrition Insecurity: training in screening and management for health professionals in Primary Health Care in the Federal District (Research, Society and Development, 2023)
Objective: to report the experience of applying the Arc of Maguerez in the training of screening and management of Food and Nutrition Insecurity for health professionals in Primary Health Care. Method: report of experience through Charles de Maguerez's Arc of Maguerez, in the perspective and adaptation of Berbel. Results and discussion: applied the five steps of the Arc of Maguerez. In which it was observed a large number of cases of families in Food and Nutrition Insecurity situation in the territory and difficulties that health professionals presented in the screening and management of such condition; key points were raised; after critical reflection, a literary search for information in the reliable database for theoretical support was performed; and hypotheses were proposed to solve the problem with their subsequent application to reality. Conclusion: the present study allowed to report a successful experience in the scope of the adequate training of health professionals to face perceived barriers and to develop competencies that cover the theme Food and Nutrition Insecurity.